Análises estratigráfica e estrutural da Seção Rifte (Valanginiano ao Barremiano) na área do levantamento sísmico 3D de baixo vermelho, Bacia Potiguar emersa - Salviano, Katiane dos Santos (2007)
Baixo Vermelho area, situated on the northern portion of Umbuzeiro Graben (onshore Potiguar Basin), represents a typical example of a rift basin, characterized, in subsurface, by the sedimentary rift sequence, correlated to Pendência Formation (Valanginian-Barremian), and by the Carnaubais fault system. In this context, two main goals, the stratigraphic and the structural analysis, had guided the research. For this purpose, it was used the 3D seismic volume and eight wells located in the study area and adjacencies. The stratigraphic analysis of the Valanginian-Barremian interval was carried through in two distinct phases, 1D and 2D, in which the basic concepts of the sequence stratigraphy had been adapted. In these phases, the individual analysis of each well and the correlation between them, allowed to recognize the main lithofacies, to interpret the effective depositional systems and to identify the genetic units and key-surfaces of chronostratigraphic character. The analyzed lithofacies are represented predominantly by conglomerates, sandstones, siltites and shales, with carbonate rocks and marls occurring subordinately. According to these lithofacies associations, it is possible to interpret the following depositional systems: alluvial fan, fluvio-deltaic and lacustrine depositional systems. The alluvial fan system is mainly composed by conglomerates deposits, which had developed, preferentially in the south portion of the area, being directly associated to Carnaubais fault system. The fluvial-deltaic system, in turn, was mainly developed in the northwest portion of the area, at the flexural edge, being characterized by coarse sandstones with shales and siltites intercalated. On the other hand, the lacustrine system, the most dominant one in the study area, is formed mainly by shales that could occur intercalated with thin layers of fine to very fine sandstones, interpreted as turbidite deposits. The recognized sequence stratigraphy units in the wells are represented by parasequence sets, systems tracts and depositional sequences. The parasequence sets, which are progradational or retrogradational, had been grouped and related to the systems tracts. The predominance of the progradation parasequence sets (general trend with coarsening-upward) characterizes the Regressive Systems Tract, while the occurrence, more frequently, of the retrogradation parasequence sets (general trend with finning-upward) represents the Transgressive System Tract. In the seismic stratigraphic analysis, the lithofacies described in the wells had been related to chaotic, progradational and parallel/subparallel seismic facies, which are associated, frequently, to the alluvial fans, fluvial-deltaic and lacustrine depositional systems, respectively. In this analysis, it was possible to recognize fifteen seismic horizons that correspond to sequence boundaries and to maximum flooding surfaces, which separates Transgressive to Regressive systems tracts. The recognition of transgressive-regressive cycles allowed to identify nine, possibly, 3a order deposicional sequences, related to the tectonic-sedimentary cycles. The structural analysis, in turn, was done at Baixo Vermelho seismic volume, which shows, clearly, the structural complexity printed in the area, mainly related to Carnaubais fault system, acting as an important fault system of the rift edge. This fault system is characterized by a main arrangement of normal faults with trend NE-SO, where Carnaubais Fault represents the maximum expression of these lineations. Carnaubais Fault corresponds to a fault with typically listric geometry, with general trend N70°E, dipping to northwest. It is observed, throughout all the seismic volume, with variations in its surface, which had conditioned, in its evolutive stages, the formation of innumerable structural features that normally are identified in Pendencia Formation. In this unit, part of these features is related to the formation of longitudinal foldings (rollover structures and distentional folding associated), originated by the displacement of the main fault plan, propitiating variations in geometry and thickness of the adjacent layers, which had been deposited at the same time. Other structural features are related to the secondary faultings, which could be synthetic or antithetic to Carnaubais Fault. In a general way, these faults have limited lateral continuity, with listric planar format and, apparently, they play the role of the accomodation of the distentional deformation printed in the area. Thus, the interaction between the stratigraphic and structural analysis, based on an excellent quality of the used data, allowed to get one better agreement on the tectonicsedimentary evolution of the Valanginian-Barremian interval (Pendência Formation) in the studied area